A meta-analysis of cognitive and functional outcomes in severe brain trauma cases - Shuanglong, Zhang; Jiangyuan, Yuan; Meng, Nie; Zheng, Wang; Yunshui, Zhang; Wei, Sun; Li, Qiao; Rongcai, Jiang (Frontiers in behavioral neuroscience, 2024)
Severe traumatic brain injuries (TBIs) are an important health issue worldwide, which are associated with harmful side effects. This meta-analysis investigates the cognitive and functional outcomes in severe brain trauma cases. It assesses the impact on memory, verbal and visual abilities, attention, learning, and the presence of depression. The study provides a comprehensive overview of the consequences of severe brain trauma injury on cognitive and functional domains. The main objective of the current comprehensive meta-analysis study is to assess and analyze the impact of severe TBI on functional and cognitive outcomes, including verbal, visual, attention, learning, memory, and emotional stability. We collected data from three online databases, including PubMed, Cochrane Library, and Embase. Case-control trials related to severe TBI association with cognitive and functional outcomes were included. Verbal strength, visual functions, learning abilities, attention, memory, and depression were considered primary outcomes. We have included 13 case-control studies with 1,442 subjects in this meta-analysis, which provide adequate data to determine the pooled effect size for targeted outcomes. The effect of severe TBI on the inducement of depression and impairment of memory, verbal, visual, attention, and learning abilities compared to the control group showed statistically significant outcomes ( < 0.05). Severe TBI is strongly associated with impaired cognitive and functional abilities, including visual and verbal disabilities, impaired memory, depression inducement, attention deficits, and learning disabilities.